Metacognitive Regulation Strategies Among Indonesian Undergraduate Students During Conic Sections Conceptualization - Yus Mochamad Cholily; Anis Farida Jamil; Mayang Dintarini (AL-ISHLAH: Jurnal Pendidikan, 2024)
Metacognitive regulation ability can assist students in abstracting the concept of a conic section. However, research exploring students’ metacognitive regulation in abstracting a mathematical concept is still rare. Thus, this study aims to analyze students' metacognitive regulation consisting of monitoring and controlling  in abstracting the conic sections concept. Three students were selected as research subjects from 26 undergraduate of mathematics education Indonesian students who were engaged in abstraction assignments. Three students were selected based on their abstraction of the conic section concept, where only one student succeeded and two students represented two types of abstraction errors present in the class. An indicator of student success in abstracting the concept of a conic section is that students can correctly identify the relationship between eccentricity and the conic curve.. After completing the task, students are given the MAI questionnaire to identify their metacognitive regulations. There were 52 items in the MAI, of which 17 items represented metacognitive knowledge and 35 items represented metacognitive regulation. Hence, this study utilized the 35 items. The paper indicates that there is a positive relationship between metacognitive regulation and abstraction processes of the three students. This relationship is particularly evident in the metacognitive monitoring component. We hypothesize that students with good metacognitive monitoring are associated with the success of the abstraction process. The findings of this study contribute to further research by suggesting that designing learning environments that support metacognitive regulation will assist students in successfully abstracting mathematical concepts.